2011
DOI: 10.1007/s00405-011-1673-0
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a smoking cessation program in the treatment protocol for patients with head and neck and lung cancer

Abstract: Smoking is the main causative factor for development of head and neck and lung cancer. In addition, other malignancies such as bladder, stomach, colorectal, kidney and pancreatic cancer have a causative relation with smoking. Continued smoking after having been diagnosed with cancer has many negative consequences: effectiveness of radiotherapy is diminished, survival time is shortened and risks of recurrence, second primary malignancies and treatment complications are increased. In view of the significant heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…This finding is consistent with other studies that have found that use of evidence-based treatments to assist with smoking cessation among smokers with cancer have not been adequately utilized [8, 22, 36]. Among highly addicted smokers more intensive smoking cessation interventions may be needed to enhance abstinence rates [37, 38]. …”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with other studies that have found that use of evidence-based treatments to assist with smoking cessation among smokers with cancer have not been adequately utilized [8, 22, 36]. Among highly addicted smokers more intensive smoking cessation interventions may be needed to enhance abstinence rates [37, 38]. …”
Section: Discussionsupporting
confidence: 90%
“…Despite high levels of nicotine dependence [85], smoking cessation rates in general cancer patients [87] and lung cancer patients [88] are comparable with "healthy" controls. For example, 40-53% of lung, and head and neck cancer patients were abstinent 6 months following treatment [89,90].…”
Section: Characteristics Of Smokers With Lung Cancermentioning
confidence: 99%
“…Characteristics of lung cancer patients who continue to smoke ∼10-13% of people still smoke 6 months following a diagnosis of lung cancer [88][89][90]. Younger age, depression, and having a household member who smokes are factors that are associated with not quitting [91].…”
Section: Characteristics Of Smokers With Lung Cancermentioning
confidence: 99%
“…The prevention of recurrence where risk factors are modifiable is far more efficacious than treating recurrent disease even when detected early . It has been recommended that patients be offered support with tobacco and alcohol cessation services as part of their follow‐up process .…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%